Peran Copywriter dalam Pembuatan Kampanye Iklan “Jakarta 101” Wisata Lokal di Jakarta - Rayhan Amelia Putri; Rizky Fauzi (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Investment encouragement is needed in the tourism sector involving participation from the community, businesses, as well as local and central governments. This collaboration is crucial to ensure a shared commitment to developing the tourism potential with sustainable growth and positive impact. The "Jakarta 101" advertising campaign has produced a video showcasing three unique local tourist destinations in Jakarta, each with its own distinct characteristics, hidden gems, and profound meanings. One of them is a coffee shop that employs individuals with disabilities, adding a unique dimension to its significance. Additionally, Jakarta boasts an educational museum with knowledgeable guides explaining its historical artifacts, along with other educational spots focused on environmental care and recycling, previously plagued by high crime rates. In this advertising campaign, a copywriter is responsible for the pre-production stages, including scriptwriting and formulating interview questions for the speakers. The copywriter plays a pivotal role in designing the advertising communication concept, maintaining brand consistency, and supporting the brand experience in various scenarios. The role of a copywriter increasingly demands digital and technological skills due to the evolving times. This research aims to enhance the skills of copywriters in creating the "Jakarta 101" advertising campaign and provide fresh insights into the role of copywriters in content creation. Copywriting in advertising holds a crucial role, serving as a bridge between potential consumers and the purchasing decision.